The crisis of governance public, corporate and international - Hughes, Owen E. (Edward Elgar Publishing, 2023)
Owen E. Hughes investigates governance across sectors including corporate, international and political governance, arguing that governance, as a general concept and an operational system, is in crisis. Hughes reasons that the crisis is in governance in general, in how societies run themselves, in how companies are run and how international organizations are run. This critical book examines the ways in which governance enables the smooth running of these societies, companies and organizations, from sub-national to international levels, and how the setting up of structures or institutional arrangements can impact this. These structures, institutions and arrangements are explored from legal, ethical and behavioural perspectives to provide a well-informed introduction to the crisis of governance. The book further examines debates over the facts, lies, science and policies behind governance, scrutinising the conflicts between democracy and autocracy in governance. The Crisis of Governance will be a beneficial resource for both undergraduate and graduate courses in public administration and management. Academics, students and scholars interested in public affairs, international politics and corporate economics will also find value in this timely book"--